An imaginary life David Malouf - Malouf, David, 1934-; Featherstone, Don, 1902-1984 (Sydney: Film Australia, 1996)
In 1996 Australian author David Malouf's ' Remembering Babylon' was considered by the MPAC literary judges to be the best novel written by anyone, anywhere, in any language, in the last three years. An imaginary life is an exploration of his life and work. The interviews with Malouf reveal his underlying belief that we have the ability to transform ourselves and change the way things
Executive producers, Chris oliver & Neil Mundy
Keywords: Authors, Australian -- 20th century -- Interviews; Australian poetry -- 20th century; Biography (Persons)